2005
DOI: 10.1161/01.cir.0000157745.46344.a1
|View full text |Cite
|
Sign up to set email alerts
|

American Heart Association and American Stroke Association National Survey of Stroke Risk Awareness Among Women

Abstract: Background-Stroke is the third leading cause of death in the United States and a major cause of morbidity in women.Awareness of risk may be an important first step in stroke prevention. The purpose of this study was to assess knowledge and awareness about stroke in a nationally representative sample of women. Methods and Results-An American Heart Association-sponsored telephone survey using random-digit dialing was conducted in June and July of 2003. Respondents were 1024 women Ն25 years of age, including an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
124
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 23 publications
4
124
1
5
Order By: Relevance
“…Several other studies of knowledge of stroke risk factors and warning signs also show consistent racial disparities. 8,9,13,14 Similar to prior reports on knowledge of stroke risk factors and warning signs, we also found that tPA awareness was lower in the oldest age groups who are at the greatest risk of stroke. 7 Limitations of this study include those associated with the Behavioral Risk Factor Survey and other random digit dial surveys.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Several other studies of knowledge of stroke risk factors and warning signs also show consistent racial disparities. 8,9,13,14 Similar to prior reports on knowledge of stroke risk factors and warning signs, we also found that tPA awareness was lower in the oldest age groups who are at the greatest risk of stroke. 7 Limitations of this study include those associated with the Behavioral Risk Factor Survey and other random digit dial surveys.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, only about 1 in 6 Michigan adults were aware of the fact that tPA therapy for stroke exists and needs to be administered within 3 hours of onset. Compared with prior estimates, Michigan's level of awareness of tPA (32%) was lower than that found in Texas (48% in Mexican Americans, and 57% in non-Hispanic whites), 8 and among U.S. women (79% to 92%), 9 but was higher than that in Cincinnati (19%). 10 Although all 4 surveys used random-digit-dial telephone methods, there were differences in time periods, populations surveyed, and question structure.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…However, less than one third of the general public can come up with more than two symptoms or risk factors and even fewer are considered to have an adequate knowledge of stroke or TIA. Similar results have been reported throughout the United States and across Europe and Asia (Kothari et al 1997, Pancioli et al 1998, Yoon et al 2001, Reeves et al 2002, Greenlund et al 2003, Parahoo et al 2003, Centers for Disease Control and Prevention 2004, Ferris et al 2005, Müller-Nordhorn et al 2006, Nedeltchev et al 2007, Evci et al 2007, Mikulík et al 2008. Women have been found to have a better overall symptom awareness and knowledge of risk factors than men (Ferris et al 2005).…”
Section: Knowledge Of Stroke Among the Publicsupporting
confidence: 75%
“…The use of IVT in ischaemic stroke has become more common, thus the public knowledge of stroke has also gradually improved. As early as in 2003, over 80% of women answering an American survey knew that in acute stroke the blood clot can be disintegrated with treatment (Ferris et al 2005). In a telephone survey conducted in 1995 and 2000, the proportion of respondents who were able to spontaneously name a stroke warning sign increased from 57 to 70% but the ability to spontaneously name a risk factor saw only a minor increase from 68 to 72% (Schneider et al 2003).…”
Section: Knowledge Of Stroke Among the Publicmentioning
confidence: 99%